Gambaran C-Reactive Protein pada Pasien Hipertensi di RSUD S.K. Lerik Kota Kupang - Marlin Sabaat; Ni Ketut Yuliana Sari; Aldiana Astuti; Agnes Rantesalu (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a noncommunicable disease that remains a public health problem because it increases the risk of cardiovascular complications. One of the mechanisms involved in the development of hypertension is the inflammatory process, which is characterized by elevated levels of C-reactive protein (CRP). This study aimed to determine the profile of CRP levels in hypertensive patients at S.K. Lerik Regional General Hospital in Kupang. A descriptive cross-sectional study was conducted on 50 hypertensive patients selected using accidental sampling. CRP testing was performed qualitatively using the latex agglutination method. The results showed that 4 samples (8%) were reactive and 46 samples (92%) were non-reactive. Reactive CRP results were equally distributed between females and males, with 2 patients (4%) each. By age group, reactive CRP was found in pre-elderly patients aged 45–59 years and elderly patients aged ≥60 years, with 2 patients (4%) in each group. All reactive CRP results were found in patients who did not regularly take antihypertensive medication (4 patients, 8%). Based on the duration of hypertension, reactive CRP was found in 3 patients (6%) with a disease duration of 1–5 years and 1 patient (2%) with a duration of 6–10 years. All reactive CRP results were found in patients with high blood pressure (≥140/90 mmHg) and stage 2 hypertension, totaling 4 patients (8%).